Power, Politics and Religion in Timurid Iran - Manz, Beatrice Forbes (Cambridge University Press, 2013)
A scholar contemplating pre-modern government must experience a sense of wonder. How was it possible to keep control over an extensive region with so few of the tools that modern governments possess? The central administration rarely held a monopoly of force, and a message sent to the other end of the kingdom could require weeks or months to arrive. The population spoke a variety of languages and most were more firmly attached to local elites than they were to the central government. Tax collection was difficult, since both landowners and peasants attempted to thwart the process. In the medieval Middle East, the challenge was particularly great, since there were few legal entities which provided society with a formal structure or regulated relationships among its separate parts. Furthermore its inhabitants included not only urban and agricultural populations but also large numbers of mountain peoples and nomads, some of whom inhabited regions almost inaccessible to government forces. Despite all this, governments did gain and hold power in the Middle East and society remained remarkably cohesive and resilient through numerous dynastic changes.